ANALISIS IMPLEMENTASI STANDAR PENILAIAN PADA JENJANG SD - Ni Made Pranyandari; Putu Desby Maharani; Ida Ayu Putu Dewi Nurheni; I Wayan Lasmawan; Ni Wayan Rati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Assessment is a crucial element of education and learning that must meet established standards to provide the best information regarding student progress. This study aims to conduct an in-depth analysis of how educators at the elementary school level implement assessment standards. Employing a qualitative descriptive approach, data were collected through in-depth interviews with teachers and school principals, direct classroom observation of assessment processes, and a review of assessment instruments and rubrics. The study was conducted at SD No. 2 Gulingan on Monday, March 2, 2026. The findings indicate that while teachers and the school have endeavored to integrate formative and summative assessments in accordance with prevailing regulations, practical implementation still faces significant challenges. Key obstacles identified include a lack of full understanding among some teachers regarding assessment procedures aligned with the *Kurikulum Merdeka* (Independent Curriculum), the presence of students scoring below the Minimum Competence Achievement Criteria, and time constraints. Therefore, optimizing assessment standards at the elementary level requires continuous support facilitated through intensive collaboration and the sharing of best practices alongside comprehensive instructional support and the simplification of grade reporting systems.